Fast band power measurement technique in Wi-Fi systems using spectrum analyzer - Bommalapati Malleswari; Mohan Kumar Sesharangaiah; Bhaskara Rao Sanka (Institute of Advanced Engineering and Science, 2022)
Fast band power measurement technique used for measuring band power in wireless fidelity (Wi-Fi) devices. The difficulty during testing the band power is burst mode transmission takes longer time to measure. A test jig or specialized tool required is costly, which allows continuous mode of transmission for power measurement. The delivered average power by a Wi-Fi device depends upon the data rate which can also vary during time. The procedure proposed hereby developed using a spectrum analyzer to measure band power in the burst mode, in order to ensure repeatable results and optimized to enable fast measurements at low cost, less time and above 90% accurate.